Subjectively Reported Symptoms in Patients with Persistent Atrial Fibrillation and Emotional Distress - Kupper, Nina; Broek, Krista; Widdershoven, Jos; Denollet, Johan (Frontiers in Psychology, 2013)
Background: Patients with atrial fibrillation (AF) are characterized by emotional distress and poor quality of life. Little is known about the relation between emotional distress and subjectively reported AF symptoms. Our aims were to compare emotional distress levels in AF patients with distress levels in the general population and to examine the cross-sectional and prospective relationship between subjective AF symptom reports and emotional distress around electrical cardioversion (ECV). Methods: At baseline, this study included 118 patients with persistent AF planned for ECV (aged 68 ± 10 years, 60% men) in which depression (BDI), anxiety (STAI), Type D personality (DS14), perceived stress (PSS-10), and AF symptoms (ATSSS) were assessed. The prospective substudy included 52 patients. Objective AF status was determined by ECG. Results: AF patients experienced significantly higher levels of anxiety (p < 0.001) and depression (p < 0.001) than age and gender matched persons from the general population. Linear regression analyses showed that AF patients with higher depression levels reported significantly more AF symptoms (β = 0.44; p < 0.0005) and reported symptoms to occur with a higher frequency (β = 0.51; p < 0.0005) during the AF episode, independent of age, sex, cardiac disease, BMI, and physical activity. At 4 weeks follow-up, 56% of all patients had maintained sinus rhythm. Repeated Measures Linear mixed modeling showed that these patients reported fewer AF symptoms and a lower frequency of AF symptoms pre and post-ECV (p = 0.04). Also, the course of the number and frequency of reported symptoms was significantly associated with the change in depression over that same time period (p < 0.0005). Conclusion: Patients with persistent AF are characterized by emotional distress. Distressed AF patients, particularly the depressed, report more AF symptoms before and after ECV. These findings call for increased attention of clinicians to emotional distress in this patient population.